Z-score model of foetal ascending aorta diameter distensibility - Chen, Fuli; Zeng, Shi; Yi, Aijiao; Chen, Lihua; Zhou, Dan; Liu, Yushan; Yao, Longmei (Frontiers in Cardiovascular Medicine, 2022)
Objective The purpose of this study is to establish Z-scores models of normal fetal ascending aorta diameter and diameter distensibility. Methods The maximum systolic diameter (Dmax), minimum diastolic diameter (Dmin), and diameter distensibility of the sinotubular junction were measured and taken as dependent variables in 490 normal fetuses at 18–40 gestational weeks, and gestational age (GA), biparietal diameter (BPD), and femoral length (FL) were taken as independent variables. The data were subjected to regression analysis, and the best-fitting equations for the dependent variables based on the independent variables were determined. The fitting equations were then applied to construct the Z-scores models. Results The Dmax, Dmin and Diameter Distensibility in normal fetuses between 18 and 40 weeks of GA could be evaluated by utilizing the Z-scores models. Dmax and Dmin increased significantly with increasing GA, BPD, and FL. Diameter distensibility, assessed as (Dmax–Dmin)/Dmin, decreased significantly with increasing GA, BPD, and FL. Conclusion The Z-scores are valuable, and can be utilized as a potent supplement to the conventional approach as they can indirectly reflect the development of fetal ascending aortic elastic property.